2001
DOI: 10.1889/1.1831851
|View full text |Cite
|
Sign up to set email alerts
|

18.5L: Late‐News Paper: low power Consumption TFT‐LCD with Dynamic Memory Embedded in Pixels

Abstract: A low power consumption Thin Film Transistor‐Liquid Crystal Display (TFT‐LCD) with dynamic memory cells embedded in each pixel using low‐temperature poly‐Si technology has been developed. By holding data in the memory, the operating rate of the data driver can be dramatically reduced to 4Hz. Eight gray scale with low power consumption can be achieved by the area‐ratio gray scale method. This TFT‐LCD can be used for displaying fine still images with low power consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…This is because the electron mobility of LTPS TFTs is higher than that of conventional amorphous silicon TFTs. Since the maximum process temperature is lower than 600°C, this technology will become more suitable to integrate the pixel array with peripheral circuits in on-panel display systems [2], [3]. Caused by the low temperature process in the fabrication and degradation by the hot carrier stress, interface states are generated at the SiO 2 /poly-Si junction interface in LTPS TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the electron mobility of LTPS TFTs is higher than that of conventional amorphous silicon TFTs. Since the maximum process temperature is lower than 600°C, this technology will become more suitable to integrate the pixel array with peripheral circuits in on-panel display systems [2], [3]. Caused by the low temperature process in the fabrication and degradation by the hot carrier stress, interface states are generated at the SiO 2 /poly-Si junction interface in LTPS TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, FPDs with built-in nonvolatile semiconductor memory ͑NVSM͒ devices have attracted a great deal of interest. Some groups [3][4][5] have carried out studies on memory embedded in the pixels of FPDs, in order to obtain low power consumption. Kimura et al 3 reported digital memory on glass technology and Tokioka et al 4 reported TFT-liquid crystal displays ͑LCDs͒ with dynamic memory embedded in the pixels.…”
Section: Introductionmentioning
confidence: 99%
“…Some groups [3][4][5] have carried out studies on memory embedded in the pixels of FPDs, in order to obtain low power consumption. Kimura et al 3 reported digital memory on glass technology and Tokioka et al 4 reported TFT-liquid crystal displays ͑LCDs͒ with dynamic memory embedded in the pixels. NVSM devices are used to enhance the brightness of a static image in FPDs, such as organic light emitting diodes ͑OLEDs͒ and TFT-LCDs, and to reduce the power consumption of glass panels and flexible displays.…”
Section: Introductionmentioning
confidence: 99%
“…When the display shows a static image, the power consumption increases, the brightness of panel degrades with time, and driving current also changes. To solve the problems about the increase of power consumption, degradation of brightness and change of driving current, dynamic memory is applied to polysilicon on the glass [1,2]. Though the dynamic memories are sufficiently worked out, suitable solutions to problems such as power consumption and the brightness of panel still remain to found.…”
Section: Introductionmentioning
confidence: 99%